Deepness: Deep neural remote sensing plugin for QGIS - Przemysław Aszkowski; Bartosz Ptak; Marek Kraft; Dominik Pieczyński; Paweł Drapikowski (SoftwareX, 2023)
This paper presents Deepness - an open-source plugin for the QGIS application, allowing the easy employment of neural network models on any raster layer representing a matrix of values or image data. Deep neural networks show a clear improvement in computer vision tasks, enabling the automatic performance of, among others, regression, segmentation and detection of objects in the images. The Deepness plugin supports model types that complete the abovementioned tasks, linking deep learning inference directly with the most popular geographic information system (GIS) application. Moreover, a model registry with ready-to-use models is provided, bringing the power of deep learning to users without machine learning expertise. This enables augmenting the familiar, established workflow with new functionalities.